The Effect of Sniper Game on Throwing Accuracy in Elementary School Physical Education - Austein Septi Dwi Maharani; Rahmat Permana; Anggia Suci Pratiwi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aimed to examine the effect of the sniper game on throwing accuracy in Physical Education, Sports, and Health (PJOK) learning among fifth-grade elementary school students. The sniper game is a target-based, play-oriented activity designed to enhance manipulative motor skills, particularly throwing accuracy. A quasi-experimental design with a pretest–posttest control group model was employed. The participants were 30 fifth-grade students of SDN 3 Sukamenak, divided into an experimental group (n = 15) and a control group (n = 15). The experimental group received PJOK instruction using the Sniper game, while the control group received conventional instruction. Data were collected through a throwing accuracy test and analyzed using descriptive statistics and paired sample t-tests at a significance level of 0.05.The results showed improvements in both groups; however, the experimental group demonstrated a greater increase in mean scores (Δ = 1.267) compared to the control group (Δ = 0.667). Statistical analysis indicated a significant effect of the sniper game on throwing accuracy (p < 0.05). These findings demonstrate that the sniper game can be effectively implemented as a game-based instructional strategy to improve throwing accuracy in elementary school PJOK learning. The scope of this study was limited to throwing accuracy; future research may explore its broader impact on other manipulative motor skills and across different educational contexts.